Поверхнева функціональна мультитекстура для фотоелектричних перетворювачів сонячної енергії - Єрохов, Валерій Юрійович (Eastern-European Journal of Enterprise Technologies, 2009)
The availability of porous silicon (PS), as material of photoelectric converters (PEC) is shown. The effective and profitable coating of PS multirexture should adapted to processes of creation of the silicon solar cells.